2020
DOI: 10.1080/19336918.2020.1764690
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia regulates human mast cell adhesion to fibronectin via the PI3K/AKT signaling pathway

Abstract: A decrease in oxygen concentration is a hallmark of inflammatory reactions resulting from infection or homeostasis disorders. Mast cells interact with extracellular matrix and other cells by adhesion receptors. We investigated the effect of hypoxia on integrin-mediated mast cell adhesion to fibronectin. We found that it was mediated by the α5/β1 receptor and that hypoxia significantly upregulated this process. Hypoxia-mediated increases in mast cell adhesion occurred without increased surface expression of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…An example of such a connection are hemidesmosomes, in which integrin α6β4 recognizes laminin in the basement membrane ( Figure 2 E) [ 4 , 123 ]. Since there are no reports in the literature on the expression of β4 integrin subunit in MCs and our own research confirmed this [ 12 ], thus formation of hemidesmosomes by MC seems to be unlikely.…”
Section: Mast Cells and Intercellular Junctionssupporting
confidence: 71%
See 2 more Smart Citations
“…An example of such a connection are hemidesmosomes, in which integrin α6β4 recognizes laminin in the basement membrane ( Figure 2 E) [ 4 , 123 ]. Since there are no reports in the literature on the expression of β4 integrin subunit in MCs and our own research confirmed this [ 12 ], thus formation of hemidesmosomes by MC seems to be unlikely.…”
Section: Mast Cells and Intercellular Junctionssupporting
confidence: 71%
“…α4β7 integrin has been documented on MC progenitors, where it is playing a crucial role in cell homing to the gut [ 29 ]. Other integrins expressed by MCs include α7 [ 27 ], αIIb [ 33 ], αE [ 35 ], α9 [ 12 , 71 ], and β6 [ 38 ] subunits. We have not found sufficient literature data confirming expression of α1, α8, α10, α11, αD, β4, and β8 integrin subunits.…”
Section: Mast Cell Adhesion Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, hypoxia can shape and induce speci c macrophage phenotypes, thereby promoting the malignant development of tumors, because hypoxia can promote immune evasion, angiogenesis, tumor cell survival and metastatic spread [28] . Hypoxia can also affect integrin-mediated adhesion of mast cells to bronectin, and the location of mast cells in tumors is related to their functions [29] . Finally, among ferroptosis-related genes, we found Aldo-Keto Reductase Family 1 Member C2 (AKR1C2), Aldo-Keto Reductase Family 1 Member C1 (AKR1C1) and Arachidonate 15-Lipoxygenase (ALOX15) that may be related to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cell culture incubators use an oxygen concentration corresponding to that in the air, which is also frequently referred to as “normoxia.” Since cell lines have been derived and cultured under such conditions, lowering the oxygen concentration to physioxic levels may be treated by these cells as hypoxia and is frequently applied as an in vitro model of hypoxia [ 1 ]. Oxygen-sensing prolyl hydroxylases (PHDs) and hypoxia-inducible factors (HIFs), such as HIF-1α and HIF-2α, are critical for initiating the cellular response to hypoxia, which includes changes in cell metabolism as well as other cellular functions, including remodeling of the extracellular matrix (ECM), cell adhesion, and migration [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%